Designing of Rectangular Photonic Crystal Fiber to Minimize the Total Dispersion - Sahay, Gunjan; Sharma, Sunil; Mathur, Aabhas; Dhabhai, Hemant (International Journal of Engineering and Technology, 2018)
Since optical fibers are extra thin strands of ultra-pure glasses which are designed to transmit lights from transmitter section to a receiver section. Such light signals can be represented as electrical signals which include audio information, videos information or various data information in any combination. Since everyone knows that an optical fiber consists of three main regions. The center region of the fiber is known as core. This core region actually used to carries light. Its diameter lies in the range from 9 micrometer (Î¼m) to 100 micrometer. In this paper I just try to design a rectangle structure of silica fiber with an alternate diameter range in every layers of the design which varies from 0.5 micrometer to 1 micrometer and kept pitch of the design is 2 micrometer. With all these parameters I found the refractive index of the designed Structure obtained is 1.433 and calculated dispersion in the 2 micrometer to 20 micrometer range is nearly zero.Â Â